Judeans in Babylonia : A Study of Deportees in the Sixth and Fifth Centuries BCE (2019)
In Judeans in Babylonia, Tero Alstola presents a comprehensive investigation of deportees in the sixth and fifth centuries BCE. By using cuneiform documents as his sources, he offers the first book-length social historical study of the Babylonian Exile. Readership: All interested in the history of Judaism, social history of the ancient Near East, and migration studies, including scholars in Biblical studies and Assyriology.